(untitled) (International Journal of Medical and Surgical Sciences, 2017)
Early Onset Neonatal Sepsis (EONS) is a clinical situation resulting from the invasion and proliferation of bacteria, fungi or viruses in the newborn (NB) bloodstream, which occurs within the first 72 hours of life. To determine the diagnostic usefulness of laboratory tests performed on infants with suspicion of early neonatal sepsis at the Santa Barbara Integrated Hospital, Honduras. A case-control study was carried out during 2016; the cases were 20 infants with early onset neonatal sepsis, and the controls were 40 infants who were admitted as potentially septic, but the blood culture result was negative. Sensitivity, specificity, positive predictive value (PPV) and negative (NPV) of leukocytosis, platelets, initial C-reactive protein (CRP) and control were calculated. Data were analyzed with SPSS version 19. It was found that 17 (28.3 %) NB were women and 43 (71.7 %) were men. The VPP of the initial PCR was 5 %, increasing to 85 % in the control study. The isolated microorganism was enterobacter in 6 (30 %) of the RNs. Of the 23 (38.3 %) neonates who presented complications; 11 (48 %) had positive blood culture and 12 (52 %) had negative blood cultures. The discharge condition was medical discharge in 55 (92 %) and referred to a more complex hospital 5 (8 %) of the neonates. The VPP of the C-reactive protein increases considerably when doing a laboratory control,between 24-48 hours.